Personal Initiative At Work: Differences Between East and West Germany - Fresé, Michael; Kring, Wolfgang; Soose, Andrea; Zempel, Jeannette (Academy of Management Journal, 1996)
Personal initiative, a concept akin to entrepreneurship and organizational spontaneity, was compared in East and West Germany. Differences were hypothesized to be the results of occupational socialization, particularly of work control and complexity, rather than of a selection effect. A representative longitudinal study was conducted in the East and a cross-sectional study in the West. Lower initiative at work was found in the East; control and complexity affected changes in initiative. The results speak for socialization and against selection.